A Brucella melitensis M5-90 wboA deletion strain is attenuated and enhances vaccine efficacy. Issue 2 (August 2015) - Li, Zhi-Qiang; Shi, Jing-Xue; Fu, Wen-Dong; Zhang, Yu; Zhang, Jing; Wang, Zhen; Li, Tian-Sen; Chen, Chuang-Fu; Guo, Fei; Zhang, Hui
Highlights The M5-90ΔwboA has low virulence in macrophages and mice. The M5-90ΔwboA can elicit an anti-Brucella-specific IgG response. M5-90ΔwboA immunizations induce a cellular response. M5-90ΔwboA immunizations induces protection against B. melitensis challenge. M5-90ΔwboA could be a potential DIVA vaccine.